Design and Development of Computerized Photoflash Method for Thermal Diffusivity Measurement - Thai, Ming Yeow (2007)
Thermal diffusivity, α is a parameter that characterizes the rate of heat diffusion in the material due to heat flux in an unsteady-state process. Flash method was introduced by Parker et al (1960) as a fast and economical method for determination of thermal diffusivity. A computerized experimental system was constructed in this project to simplify and expedite the experimental process for determination of thermal diffusivity of solid samples at room temperature. In conventional photoflash method, a high intensity photoflash was used as the energy pulse source. A thermocouple wire was used to monitor the temperature of the rear surface of the sample and captured by an oscilloscope. The calculation of thermal diffusivity value could be done either manually or with the aid of several software tools. The present work replaces these lengthy processes by automating the firing of the photoflash and the capturing of temperature-time data of the sample rear surface. A Personal Computer equipped with a National Instrument DAQ (Data Acquisition) card plays its role as a control center to control and monitor the experiment process from firing of flash to the completion of thermal diffusivity determination. Various electronics circuits were studied and developed in order to facilitate the firing of flash such as relay driver circuits, photodiode amplifier and Schmitt Trigger circuit. The circuit interacts with the DAQ card to perform specific functions such as triggering acquisition or switching on the flash. An event-driven application called ThermDiff was written using Microsoft Visual Basic 6 allowing the user to control the experimental operations interactively. The application provides a complete set of functions to the user include hardware control, data acquisition, data conditioning and computation of thermal diffusivity value. Besides, other features such as file storage, graphical presentation, printing and help system are included into the application. The functionality and workability of the computerized experimental system were successfully tested. The reliability and accuracy was verified by testing several samples of known thermal diffusivity value: Aluminum, Silicon Carbide and Boron Carbide. As results, the computed thermal diffusivity values showed close agreements to the literature values with difference of less than ±5%. It is recommended that future researches can be carried out to develop a computerized experimental system that is capable to determine thermal diffusivity value accurately at various temperatures.